Asthma, atopy and serious psychological distress: prevalence and risk factors among young people in the Melbourne atopy cohort study. (1st December 2020) - Barton, Christopher A.; Dharmage, Shyamali C.; Lodge, Caroline J.; Abramson, Michael J.; Erbas, Bircan; Lowe, Adrian
Abstract: Background: While atopic conditions are associated with increased risk of mental health problems, the evidence that a range of allergic conditions are associated with psychological distress in young people is less clear. Methods: We recruited a longitudinal birth cohort study of 620 children with a family history of allergic disease. At the 18-year follow up, atopic sensitization was determined by skin prick testing. Surveys were used to determine psychological distress (Kessler 6), quality of life (SF12), respiratory symptoms and management, presence of current eczema and hay fever. Regression models were used to identify predictors of psychological distress and quality of life, while controlling for potential confounders. Results: Prevalence of serious psychological distress was quite low ( n = 22, 5.3%), and there were no associations between psychological distress and current atopic sensitization, symptoms of hay fever, eczema or asthma. Smoking status and lower level of maternal education were associated with lower physical quality of life (SF12 PCS subscale). Psychological distress total score, lower maternal education, smoking, female sex, and current eczema were associated with worse mental quality of life (SF12 MCS subscale). Conclusion: We found relatively low levels of psychological distress in this cohort of young adults, despite a high prevalence of allergic diseases. Positive social factors may serve to buffer psychological distress amongst the cohort accounting for the low prevalence of serious psychological distress observed.